Teh putih (Camellia sinensis) dan kelor (Moringa oleifera) sebagai antihiperglikemia pada tikus Sprague dawley yang diinduksi streptozotocin - Rahma, Amalia; Martini, Rina; Kusharto, Clara Meliyanti; Damayanthi, Evy; Rohdiana, Dadan (Jurnal Gizi dan Pangan, 2017)
This study aims to examine the antihyperglycemic effect of white tea (Camellia sinensis) and Moringa oleifera when administered as a single component and as mixture in streptozotocin-induced diabetic rats. The study design was experimental. The first step was to analyze epigallocathecingallat (EGCG) content as standard with High Performance Liquid Chromatography (HPLC) method. The second step was intervention in Sprague dawley rats induced by streptozotocin 40 mg/kgBW. Intervention held for 21 days with given white tea (WT), M. oleifera (MO), mixture of white tea and M. oleifera (WT+MO) and green tea (GT) as positive control with reference dose 100 mg/kgBW EGCG. Rats blood glucose and body weight were measured. The results are WT having the highest content of EGCG (4.46%). MO and WT+MO only have 2.42% and 2.46% of EGCG while GT as control is the lowest (1.29%). Measurements of blood glucose and body weight in group that given WT or MO as single component showed no significant difference with control negative group (p>0.05). Blood glucose decreased significantly in group WT+MO (p<0.05). Administration of WT+MO was able to maintain a stable body weight during the intervention period (p>0.05). The combination of white tea and M. oleifera has better ability as an antihiperglycemic agent compared to single component.